2012
DOI: 10.3109/15563650.2012.705847
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fructose-1,6-diphosphate on haemodynamic parameters and survival in a rodent model of propranolol and verapamil poisoning

Abstract: FDP improved survival for both toxicants with an improvement in haemodynamics at the higher dose in propranolol poisoning. Future research could examine the efficacy of FDP in other beta-blocker and calcium channel-blocker poisoning as well as in concert with established inotropic therapies in drug-induced cardiovascular collapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“… 138–140 Animal studies showed conflicting results for the use of carnitine. 153–155 Finally, only animal studies were found for the following interventions: Bay K 8644 and CGP 28932, 100 , 101 , 103 digoxin, 141–143 cyclodextrin, 144 , 145 suggamadex, 146 liposomes, 147 , 148 bicarbonate, 149 fructose 1,6-diphosphate, 150 PK11195 151 and triiodothyronine. 152 …”
Section: Resultsmentioning
confidence: 99%
“… 138–140 Animal studies showed conflicting results for the use of carnitine. 153–155 Finally, only animal studies were found for the following interventions: Bay K 8644 and CGP 28932, 100 , 101 , 103 digoxin, 141–143 cyclodextrin, 144 , 145 suggamadex, 146 liposomes, 147 , 148 bicarbonate, 149 fructose 1,6-diphosphate, 150 PK11195 151 and triiodothyronine. 152 …”
Section: Resultsmentioning
confidence: 99%
“…F6P is an important phosphorylated carbohydrate involved in the non-oxidative pentose phosphate pathway and is of particular interest for the study of various metabolic diseases. F6P is also an important precursor for the production of d -fructose-1,6-diphosphate and various other phosphate sugars with important therapeutic values for the treatment of sickle cell anemia, congestive heart failure, myocardial infarction, and neurodegenerative disease [ 14 , 15 ]. To obtain F6P in a sufficiently large quantity, a less expensive high-yield production method must be developed.…”
Section: Resultsmentioning
confidence: 99%
“…F6P is also an important precursor for the production of d -fructose-1,6-diphosphate via phosphofructokinase 1 catalysis [ 13 ]. d -fructose-1,6-diphosphate has proven therapeutic potential; clinical data show that this carbohydrate may be useful in a variety of ischaemic conditions, reduction of ischaemic injury in sickle cell anemia, congestive heart failure, bypass surgery, myocardial infarction, and organ preservation for transplantation [ 14 , 15 ]. Other important molecules such as glyceraldehyde-3-phosphate and dihydroxyacetone phosphate have medicinal value (candidate drugs for the treatment of degenerative diseases) and can be obtained in a cascade reaction from fructose-1,6-diphosphate with the help of fructose 1,6-bisphosphate aldolase [ 12 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It increases the production of ATP in conditions where phosphofructokinase is inhibited (e. g. by lactate) and preserves its own macroergic cell phosphates for pre-phosphorylation of hexoses. The relative ATP production by anaerobic glycolysis is greater for FDP than glucose [29,30].…”
Section: Discussionmentioning
confidence: 96%
“…Analyzing the clinical effects of FDP, several authors noted that it may restore inhibited glycolytic activity in the ischemic myocardium by regulating the effect on the glycolytic pathway, and also be a substrate for this pathway. Other researchers have shown that FDP reduces the area of tissue ischemia in experimental cerebral and myocardial infarction and improves hemodynamics after cardiac bypass [30]. Some data have demonstrated the absence of hypotensive effect of FDP that allows using it in patients with shock conditions and unstable hemodynamics [15].…”
Section: Discussionmentioning
confidence: 99%